Legitimasi Kekuasaan atas Sejarah Keruntuhan Kerajaan Majapahit dalam Wacana Foucault - Muhammad Iqbal Birsyada (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
The history of the collapse of the Majapahit showed the discourse of power. In this context  rule has been supporting a particular version of historical knowledge. Applying  historical method and multi-dimensional approach, this study aims to find out why the knowledge about the collapse of Majapahit spreading among community members was more tended toward the version that Girindrawardhana  as a single actor who overthrow Prabu Brawijaya V. The results of this study indicated  that the knowledge  among Javanese  community about the collapse  of Majapahit that stated Girindrawardhana as the sole actor that attacked  and subverted  the kingdom of Majapahit which at the time was ruled by King Kertabhumi (Brawijaya V) is supported by a wide range of all power of the ruling elite that were largely due to ideological motives. Power and ideology are used as a means of legalizing knowledge.